2004
DOI: 10.1007/s00125-004-1537-x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the resistin gene is associated with obesity and insulin-related phenotypes in Finnish subjects

Abstract: Aims/hypothesis. Resistin is a peptide hormone produced by adipocytes that is present at high levels in sera of obese mice and may be involved in glucose homeostasis through regulation of insulin sensitivity. Several studies in humans have found associations between polymorphisms in the resistin gene and obesity, insulin sensitivity and blood pressure. An association between variation in the resistin gene and Type 2 diabetes has been reported in some, but not all studies. The aim of this study was to analyse v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
59
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 28 publications
8
59
1
Order By: Relevance
“…Defects in the melanocortin pathway are related to severe obesity (12). Similar results were obtained for leptin receptor mutations (13), variations of the resistin gene (14), and the adiponectin locus (15). In Germans, Chinese, and South Africans, the 825T allele of the gene GNB3 encoding the G-protein b3 subunit is significantly associated with obesity with odds ratios (ORs) between 2 and 3 (16).…”
Section: Introductionmentioning
confidence: 61%
“…Defects in the melanocortin pathway are related to severe obesity (12). Similar results were obtained for leptin receptor mutations (13), variations of the resistin gene (14), and the adiponectin locus (15). In Germans, Chinese, and South Africans, the 825T allele of the gene GNB3 encoding the G-protein b3 subunit is significantly associated with obesity with odds ratios (ORs) between 2 and 3 (16).…”
Section: Introductionmentioning
confidence: 61%
“…Adiponectin is produced predominantly by peripheral adipose tissue, and resistin is produced by visceral adipose tissue. Adiponectin improves insulin sensitivity whereas resistin worsens it in rodent studies (16,17), with conflicting results in humans (18)(19)(20). Although a recent study by Meigs and colleagues did demonstrate that insulin resistance in humans was inversely related to adiponectin and positively related to resistin (21).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although some studies suggest a link between resistin and insulin sensitivity [19] others have failed to show an association with insulin resistance [16,20,21]. Similarly, genetic analyses have suggested that resistin plays a role in the aetiology of insulin resistance and diabetes [22,23], whereas others contest this view [24].…”
Section: Introductionmentioning
confidence: 99%